Determinan Manajemen Pajak Pada Perusahaan Aneka Industri - Amalia Indah Fitriana; Hendra Galuh Febrianto; Dede Sunaryo (Journal of Business and Economics Research (JBE), 2022)
The purpose of this study was to determine the effect of the intensity of fixed assets, independent commissioners and leverage on tax management in various industrial companies listed on the Indonesia Stock Exchange (IDX). The research time period used is 5 years, namely the 2017-2021 period. The population of this study includes all companies of various industries listed on the IDX. The sampling technique used purposive sampling technique. Based on the predetermined criteria obtained 10 companies. The type of data used is secondary data obtained from the IDX website. The analytical method used is panel data regression analysis supported by the Eviews 9 program. The results show that the intensity of fixed assets and leverage have a positive effect on tax management and independent commissioners have no effect on tax management.